PENGARUHSTRORE IMAGE DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING(STUDI PADA KONSUMEN ROBINSON DEPARTMENT STORE MAL CIPUTRA SEMARANG - Suprapto, Ristyana Prabasari; Saryadi, Saryadi; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
A fantastic development of the human need for clothing and current fashion era demands the modern retail to seek strategies to meet the needs of the consumer's desires. Recently, Robinson Department Store not stand as the only modern retail, especially in Semarang. The presence and development of other modern retails are supposed to make Robinson Department Store swiftly and began designing appropriate strategies and innovative products that can endure and must remain attractive to customers, so the companyâ€™s purpose which is increasing products sales can be achieved. But in 2014, Robinson Department Store Mal Ciputra Semarangâ€™s sales profit has been decreased. Based on preliminary studies, poor quality products, less diverse products, unattractive store decoration, and unattractive arrangement of products display are found to be reasons that do not support consumers to impulse buying at Robinson Department Store Mal Ciputra Semarang.This study aims to determine the effect of Store Image and Store Atmosphere towards Impulse Buying of The Costumer ofÂ Robinson Department Store Mal Ciputra Semarang.Data collection techniques using purposive sampling with a sample of 100 consumers.Quantitative data were analyzed using SPSS version 15. Data were analyzed through the validity, reliability, crosstab, product moment correlation, coefficient of determination, simple linear regression, multiple linear regression, t test and F test. The results showed that, Store Image has a significant effect on the Impulse Buying. Store Atmosphere has a significant effect on Impulse Buying. Then simultaneously, Store Image and Store Atmosphere have significant effect on Impulse Buying. Based on the multiple regression test, the result of the beta coefficient of Store Image shows the number 0.301, while the Store Atmosphere indicates the number 0.489. Store Atmosphere provides the most effect on Impulse Buying at Robinson Department Store Mal Ciputra Semarang.Enhancements of Store Image can be done by improving the quality and diversity of products, services of the employee (salesman), and decorations.Besides the enhancements of Store Atmosphere can be done through scent, cleanliness, colors and lighting of the room, and music. Through those things, the intention of impulse buying by consumers is expected to be increased in Robinson Department Store Mal Ciputra Semarang.